A behaviour-based approach to the assessment of cue utilisation: implications for situation assessment and performance. (2nd January 2021) - Wiggins, Mark W.
Abstract: Although the utilisation of cues is widely recognised as essential for skilled situation assessment, it is a construct that is difficult to evaluate due to the idiosyncratic and nonconscious nature of cues. This raises risks for high consequence organisations where there is an expectation that operators are capable of accurate and timely situation assessment. The objective of this paper was to articulate the development and evaluation of novel, behaviour-based approach to the assessment of cue utilisation. Explorations that are based on this approach have yielded consistent outcomes in differentiating higher from lower performance across a range of operational domains, including transmission power control, paediatric intensive care, audiology, and aviation. Opportunities are proposed for further research to explain the inherent cognitive mechanisms involved and better model the performance of operators under a range of environmental conditions.